2015
DOI: 10.1007/s13524-015-0425-y
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Stability of Marital and Cohabiting Unions Following the Birth of a Child

Abstract: The share of births to cohabiting couples has increased dramatically in recent decades. How we evaluate the implications of these increases depends critically on change in the stability of cohabiting families. This study examines change over time in the stability of U.S. couples who have a child together, drawing on data from the 1995 and 2006-2010 National Survey of Family Growth (NSFG). We parse out the extent to which change in the stability of cohabiting and married families reflects change in couples' beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 57 publications
(83 reference statements)
1
52
0
4
Order By: Relevance
“…"Across Europe, higher educated individuals are more likely to marry before a birth (Mikolai et al 2016), and lower educated individuals are more likely to separate after a birth (Musick and Michelmore 2015)" (Chapter 4). Thus while she rightfully calls for more research to understand the complex relationships between context, selection, socially constructed meanings of cohabitation and marriage, and changes over individual life courses, she does point to an important similarity between the United States and Europe: Childbearing within marriage occurs more often among the advantaged.…”
Section: Exploring the Causes Of Increasingly Unequal Family Lifementioning
confidence: 99%
See 2 more Smart Citations
“…"Across Europe, higher educated individuals are more likely to marry before a birth (Mikolai et al 2016), and lower educated individuals are more likely to separate after a birth (Musick and Michelmore 2015)" (Chapter 4). Thus while she rightfully calls for more research to understand the complex relationships between context, selection, socially constructed meanings of cohabitation and marriage, and changes over individual life courses, she does point to an important similarity between the United States and Europe: Childbearing within marriage occurs more often among the advantaged.…”
Section: Exploring the Causes Of Increasingly Unequal Family Lifementioning
confidence: 99%
“…This group has experienced a surge of births within cohabiting unions. Unlike the typical cohabiting unions in some European countries, these unions tend to be brittle and to lead to disruptions at a high rate (Musick and Michelmore 2015). Among moderately educated married couples (those with secondary-school diplomas), there has not been as much decline in divorce as among the highly educated (S. P. .…”
Section: How Inequality Drives Family Formation 73mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being more prevalent, cohabiting unions have also become less stable overall, with fewer of them transitioning to marriage and more of them dissolving over a three-year period (Guzzo 2014). But Musick and Michelmore (2015) showed that dissolution rates specific to cohabiting couples with children have declined over time, leading to fewer children in cohabiting unions exposed to parental change than in the past. The increase in children born to unmarried parents suggests children may be exposed to more household changes in the 2000s and 2010s than in the 1980s and 1990s (Brown, Stykes, and Manning 2016), whereas more union stability among married and cohabiting parents of children suggests a countervailing force of stability, leading to less exposure to household change over time.…”
Section: Accounting For Social Changementioning
confidence: 99%
“…These findings by family structure and race and ethnicity result from a pooled analysis of all seven SIPP panels, but there is reason to suspect that the proportion of children exposed to changes in household composition may have changed over time as the marital and cohabiting unions containing children have become more stable over time (Kennedy and Ruggles 2014;Musick and Michelmore 2015). …”
Section: Heterogeneity In Change By Family Structure and Racementioning
confidence: 99%